Microbiological analysis of tongue dorsum coating in patients hospitalized in ICU - Alexandre Franco MIRANDA; Ana Luiza Ferreira de ARRUDA; Daiane Cristina PERUZZO (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT Objective: ssess quantitatively and qualitatively tongue coating microbiota in ICU patients. Methods: Analytical observational study, convenience sample comprising 65 patients was included for medical report analysis and collection of general data, tongue coating assessment through visual inspection and microbiological sample collection for further laboratory analysis. The collection was performed by a single examiner using a sterile swab introduced and rubbing the posterior portion of the tongue close to the oropharynx. Results: Most patients (60%) belonged to the female sex, at mean age of 74.2 years. The main reasons for hospitalization were lung issues (26.2%) - prevailing associated comorbidities were diabetes (43.1%) and high blood pressure (66.2%). The mean length of stay in the ICU was one day. All patients presented tongue dorsum coating. There were Candida albicans (37%), Streptococcus parasanguinis (26.1%) and Streptococcus mitis (32.6%) in 1/3 of lingual extension. Streptococcus mitis (p=0,0265) was the most prevalent species. Conclusion: There was no significance between the amount of coating and number of observed species, although all assessed patients had presented coating. The most prevalent microorganisms were Candida albicans, Streptococcus parasanguinis and Streptococcus mitis.